Integration of Oral Health and Primary Care Practice: An Interprofessional Approach - Emily Zimmerman (Association of American Medical Colleges, 2015)
Abstract Introduction The purpose of interprofessional oral health simulations is to promote the development of interprofessional oral health core clinical competencies. This is accomplished here through three team-based simulation case studies pairing dental and speech-language pathology (SLP) students towards the common goal of exchanging clinically relevant information to identify and implement appropriate care for patients, with the overarching goal being to improve oral health. Methods SLP and dental students worked together to complete three simulations. These simulations covered (1) acute dental injury resulting in missing teeth, (2) ankyloglossia, and (3) tongue thrusting. Each simulation experience consisted of a standard actor and a 3-D dental mold representing the dental issue. The student pairs discussed what they saw in terms of the oral mechanism and combined this with the patient's description to fully assess the client. Results Students found this to be a valuable experience, albeit occasionally uncomfortable, as they worked together in teams for the first time to diagnose and treat clients. Students reported that they had never had this kind of experience before and that the experience improved their confidence as future clinicians. The oral health simulations were very effective. This information is based on feedback from the students and the standardized actors. Discussion These simulations have been a valuable experience for both the undergraduate SLP students and the dental students. Although many of the students reported leaving the simulation feeling more confident of their clinical knowledge than they had been before, practicing a few clinical experiences in class in small groups would have been a beneficial presimulation background training. Additionally, while the standard actors were trained broadly on their dental issue and the case study, in retrospect everyone would have benefited from more-specific training regarding the dental and speech consequences of the case studies and appropriate treatment plans.